Effect of inspiratory flow rate on bronchomotor tone in normal and asthmatic subjects. Issue 2 (February 1984) - Hida, W; Arai, M; Shindoh, C; Liu, Y N; Sasaki, H; Takishima, T
Abstract : The effect of the inspiratory flow rate during deep inspiration on the regulation of bronchomotor tone was studied in nine normal and 22 asthmatic subjects. Changes in bronchial tone were assessed by respiratory resistance measured by an oscillation method. In normal subjects with bronchoconstriction induced by methacholine a rapid deep inspiration reduced respiratory resistance more than a slow deep inspiration. Asthmatic subjects with spontaneous airway narrowing showed an increase in respiratory resistance after deep inspiration that was greater after rapid than after slow deep inspiration. On the other hand, in asthmatics with methacholine induced bronchoconstriction, bronchodilatation occurred after deep inspiration and this was also greater after rapid than after slow deep inspiration. Lignocaine inhalation attenuated both bronchoconstriction and bronchodilatation induced by both slow and rapid deep inspiration. These results suggest that the effects of deep inspiration are mediated at least in part via receptors in the airways. It is suggested that in asthmatic patients with spontaneous bronchoconstriction irritant receptor activity will be increased in proportion to the speed of inspiration. After methacholine induced bronchoconstriction stretch receptor activity is likely to behave in a similar fashion, leading to an opposite effect.